2016
DOI: 10.1590/1983-40632016v4638374
|View full text |Cite
|
Sign up to set email alerts
|

Response of soil fungi and biological processes to crop residues in no-tillage system

Abstract: Soil management and crop rotation can directly affect the soil microbial community. This study aimed at determining soil quality indicators and soilborne fungi in a no-tillage system. A randomized blocks design, in a 3 × 2 factorial arrangement, was used. Three cover crops (palisade grass, millet and common bean) provided straw and root residues to the following crops of corn and soybean. The common bean-soybean sequence provided little soil covering and higher metabolic quotient and soil basal respiration and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Soratto et al (2013b), studying early N application for the sowing of common bean, also found that its yield was little influenced by the previous cropping system (maize and maize intercropped with U. ruziziensis grass). In addition, it should be considered that agricultural systems are complex, which requires a holistic view of the processes and impacts of these agroecosystems (PANKHURST et al, 1995, OLIVEIRA et al, 2016. However, in the splitting schemes 30-60-00, 30-00-60, 00-60-30 and 00-45-45, this attribute was superior when the common bean was cultivated in succession to maize as single crop and intercropped with U. ruziziensis grass.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Soratto et al (2013b), studying early N application for the sowing of common bean, also found that its yield was little influenced by the previous cropping system (maize and maize intercropped with U. ruziziensis grass). In addition, it should be considered that agricultural systems are complex, which requires a holistic view of the processes and impacts of these agroecosystems (PANKHURST et al, 1995, OLIVEIRA et al, 2016. However, in the splitting schemes 30-60-00, 30-00-60, 00-60-30 and 00-45-45, this attribute was superior when the common bean was cultivated in succession to maize as single crop and intercropped with U. ruziziensis grass.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, studies suggest the effect of exudates of the roots of this forage on N cycling, suppressing the processes of nitrification and leaching (GOPALAKRISHNAN et al, 2009). N is the most required nutrient by common bean, which needs 30 to 45 kg of N for every 1,000 kg of grains (OLIVEIRA;THUNG, 1988). Due to the shallow root system and short cycle, the requirement for readily available N during the initial stages is higher for this crop.…”
Section: Introductionmentioning
confidence: 99%
“…The chitinase enzyme is a pathogenesis-related protein known as PR-Protein. This enzyme has antifungal properties, can inhibit spore germination and induce fungal cell wall lysis (Oliveira et al, 2016).…”
Section: Introductionmentioning
confidence: 99%